Towards closure at Jabiluka: rehabilitation of the Boiweg-Almudj sacred site complex - Smith, HD; Thompson, A (Mine Closure 2013: Proceedings of the Eighth International Seminar on Mine Closure, 2013)
Jabiluka is an underground uranium deposit of significant economic potential located within the contiguous cultural and natural environments in Australia known as Kakadu National Park. Following a period of public controversy in the late 1990s, the development of the mine was shelved and the site was placed into care and maintenance without any ore being processed. Traversing Jabiluka is a significant complex of sacred Aboriginal sites known as Boyweg-Almudj, which was where pre-mining drilling activities were undertaken in the 1970s. This paper considers the damage that has been done to Boyweg-Almudj from the traditional Aboriginal owners’ perspective and the steps that have been taken since 2010 to have this area rehabilitated. The outcomes are discussed not only in respect of environmental benefit, engagement and cultural acceptance but also in terms of the application of traditional Aboriginal knowledge to the remediation and cultural reclamation of the Jabiluka site. These actions constitute part of an evolving model for integrating Aboriginal and non-Aboriginal knowledge into the closure of mine sites across Australia’s Northern Territory that has been in development since 2006.